The role of European Federation of Clinical Chemistry and Laboratory Medicine Working Group for Preanalytical Phase in standardization and harmonization of the preanalytical phase in Europe. (September 2016) - Cornes, Michael P; Church, Stephen; van Dongen-Lases, Edmée; Grankvist, Kjell; Guimarães, João T; Ibarz, Mercedes; Kovalevskaya, Svetlana; Kristensen, Gunn BB; Lippi, Giuseppe; Nybo, Mads; Sprongl, Ludek; Sumarac, Zorica; et al.
Patient safety is a leading challenge in healthcare and from the laboratory perspective it is now well established that preanalytical errors are the major contributor to the overall rate of diagnostic and therapeutic errors. To address this, the European Federation of Clinical Chemistry and Laboratory Medicine Working Group for Preanalytical Phase (EFLM WG-PRE) was established to lead in standardization and harmonization of preanalytical policies and practices at a European level. One of the key activities of the WG-PRE is the organization of the biennial EFLM-BD conference on the preanalytical phase to provide a forum for National Societies (NS) to discuss their issues. Since 2012, a year after the first Preanalytical phase conference, there has been a rapid growth in the number of NS with a working group engaged in preanalytical phase activities and there are now at least 19 countries that have one. As a result of discussions with NS at the third conference held in March 2015 five key areas were identified as requiring harmonisation. These were test ordering, sample transport and storage, patient preparation, sampling procedures and management of unsuitable specimens. The article below summarises the work that has and will be done in these areas. The goal of this initiative is to ensure the EFLM WG-PRE produces work that meets the needs of the European laboratory medicine community. Progress made in the identified areas will be updated at the next preanalytical phase conference and show that we have produced guidance that has enhanced standardisation in the preanalytical phase and improved patient safety throughout Europe.